Prevalência da deficiência de vitamina D e fatores associados em trabalhadores - Sena, Elisama Araújo de (2019)
Prevalence of vitamin D deficiency and its associated factors has been extensively investigated and determined in population studies of metropolitan regions. However, regardless of the region, there are subpopulations that are exposed to risk or protection factors, which may modify existing studies. Workers of the various companies are exposed to regimes that deprive the sun, impose different dietary habits and these factors may cause vitamin D levels to be different from the population in which they are. Interesting working environment are the Food and Nutrition Units, which work with the production and distribution of food for sick and / or healthy group. In this way, this study is pertinent, because the Food and Nutrition Unit workers are associated with risk factors. The study aimed to estimate the prevalence of vitamin D deficiency and its associated factors in food and nutrition unit workers at a university campus. Epidemiological study of the case series type. Participants were classified according to their working regime in a closed environment, in a modified daytime (12 / 36h) and daily diurnal (9h and 48min), and were submitted to five stages of data collection, where the sociodemographic data (C-reactive protein, alpha acid glycoprotein, serum calcium, parathyroid hormone, 25-hydroxyvitamin D) were used in the study, . Data were categorized and reported by absolute and relative frequency. Bivariate associations were examined using contingency tables and the chi-square test with continuity correction. A robust variance Poisson regression model was used to estimate the crude and adjusted prevalence ratio and their respective confidence intervals. Only variables with P <0.20 in the bivariate analysis were included in the fit of the model. Analyzes were run on IBM SPSS. In the sample of 91 participants, the prevalence of vitamin D deficiency was 16.5% (n = 15). There were significant associations between vitamin D and service time (χ2 = 4.50, P = 0.034), work regime (χ2 = 23.60, P = 0.001) and sun exposure when going to work (χ2 = 6.53; P = 0.011). There were no significant associations between vitamin D and sociodemographic, anthropometric, nutritional, biochemical, and calcium and vitamin D variables. In the regression analysis, only the work regimen showed a significant association with vitamin D, both in the crude analysis, as the adjusted value. These findings indicated that workers with daytime work hours 9h and 48min / day (49h / week) had 1.33 (1.11-1.59) times more chance of having vitamin D deficiency compared to the work regime diurnal alteration of 12h / 36h (36h or 48h/week) (P = 0.001). It is concluded that despite the low prevalence of vitamin D deficiency in these workers, the work regimen was shown to be a risk factor for vitamin D deficiency in this population.